ANALISIS KINERJA KEUANGAN SEBAGAI ALAT PENENTUAN PERINGKAT BANK PADA KANTOR CABANG PD BPR NTB LOMBOK TIMUR - MUH. KARYADI; Suparlan, SE., M.Sc.A Suparlan (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2019)
This study aimed to analyze the financial performance and do peringkatan Branch PD BPR East Lombok NTB to make use of financial ratios ROA, ROA,LDR, NIM, NPL. The sampling technique in a study conducted with a saturated sampling technique so that all branch offices PD BPR East Lombok NTB into the sample yakitu Branch Office Dasan Lekong, Sambalia, Lombok, Paok cut, Aikmel, Kota Raja and Montong Betok. The data used in the data years 2010-2012 were calculated using financial ratios ROA, ROA, LDR, NIM, NPL. Each of these financial ratios given the weight of each 20%, after weighting is given then it will do the ranking. The rating in 2010 put in order from the highest position of Branch Office Dasan Lekong, King City, Lombok, Sambalia, Montong Betok, Paok cut and Aikmel. In the year 011 put in sequence from the highest position of Branch Office Dasan Lekong, Sambalia, Lombok, Aikmel, Montong Betok, Paok cut and King City. In 2011 puts in sequence from the highest position of Branch Office Paok cut, Lombok, Sambalia, Dasan Lekong, Aikmel, Montong Betok and King City. Cumulatively for the whole of the period 2010-2012 sequentially placing the highest position of Branch Office Dasan Lekong, Sambalia, Lombok, Paok cut, Aikmel, Kota Raja and Montong Betok.